A two-phase point-of-care diagnostic device for bladder cancer - Jeong, Youngdo (NATURE PUBLISHING GROUP, 2025)
Point-of-care diagnostic kits for detecting bladder cancer using urine enable screening and surveillance to be carried out at home. We demonstrate a point-of-care diagnostic device with a two-phase system that uses buoyant signal transducers to allow the direct use of untreated urine for screening, providing enhanced accuracy and ease of use over existing methods.